2021
DOI: 10.3390/app11052437
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermal Effects of Radiofrequency Ablation Mediated with Iron Oxide Nanoparticles Dispersed in Agarose and Chitosan Solvents

Abstract: Thermal ablation (TA) is known as an alternative therapy to surgery to treat tumors. However, TA-based therapy requires advanced approaches in order to prevent causing damage to healthy tissue around the tumor and selectively target the desired area. Nanoparticles are considered as a promising tool in biomedicine to fulfill these requirements. This study was carried out in order to analyze the effect of iron oxide nanoparticles on the temperature increment during radiofrequency ablation therapy of porcine live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Under this condition, medical generators enter a "safe mode", discontinuing the power supply and interrupting the RFA procedure [25]. In order to improve over this effect, both agarose and chitosan gels [26] have been employed in order to reduce the tissue impedance. In addition, gold and silver nanomaterials [27] have been used in combination with agarose with the purpose of improving the thermal delivery, and ultimately increasing the ablated region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this condition, medical generators enter a "safe mode", discontinuing the power supply and interrupting the RFA procedure [25]. In order to improve over this effect, both agarose and chitosan gels [26] have been employed in order to reduce the tissue impedance. In addition, gold and silver nanomaterials [27] have been used in combination with agarose with the purpose of improving the thermal delivery, and ultimately increasing the ablated region.…”
Section: Introductionmentioning
confidence: 99%
“…Prior works were performed on RFA using ferromagnetic nanoparticles [26], and silver nanoparticles with a green-oriented synthesis method [40], showing an increase of the treated region when nanoparticles are inserted in situ in a solution of agarose or chitosan gel. However, gold nanoparticles (AuNP) represent the most popular method to extend the performance of thermotherapies, as AuNP have been demonstrated in radiofrequency [41] and laser [42] ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Ashikbayeva et al have presented that magnetic nanoparticles increase the ablation size and temperature rise when various concentrations from 1 to 10 mg /mL of magnetic nanoparticles are injected onto a porcine liver in 2021. The core tempereture in the nanoparticle injected phantom liver at 5 mg/mL concentration become 142 °C [18]. In the same year, Zhou et al has found out microwave ablation-induced antitumor immune responses are boosted by mannose-derived carbon dots, which capture and convey "danger signals" to dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The non-metallic composition of fiber-optic sensors prevents the sensors from electromagnetic interference and corrosion [ 21 ]. Recent achievements in the field of fiber-optic sensors made it possible to implement multi-point temperature-sensing opportunities in space by integrating the sensing elements into a single optical fiber [ 24 , 25 , 26 ]. Two approaches utilize multiplexed sensing with a high spatial resolution that is vital in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%